Are brain responses to emotion a reliable endophenotype of Schizophrenia?: an image-based functional magnetic resonance imaging meta-analysis - Fiorito, Anna; Aleman, André; Blasi, Giuseppe; Bourque, Josiane; Cao, Hengyi; Chan, Raymond C. K.; Chowdury, Asadur; Conrod, Patricia; Diwadkar, Vaibhav A.; Goghari, Vina M.; Guinjoan, Salvador; Gur, Raquel E.; et al. (Biological psychiatry, 2023)
Background - Impaired emotion processing constitutes a key dimension of schizophrenia and a possible endophenotype of this illness. Empirical studies consistently report poorer emotion recognition performance in patients with schizophrenia as well as in individuals at enhanced risk of schizophrenia. Functional magnetic resonance imaging studies also report consistent patterns of abnormal brain activation in response to emotional stimuli in patients, in particular, decreased amygdala activation. In contrast, brain-level abnormalities in at-risk individuals are more elusive. We address this gap using an image-based meta-analysis of the functional magnetic resonance imaging literature. - Methods - Functional magnetic resonance imaging studies investigating brain responses to negative emotional stimuli and reporting a comparison between at-risk individuals and healthy control subjects were identified. Frequentist and Bayesian voxelwise meta-analyses were performed separately, by implementing a random-effect model with unthresholded group-level T-maps from individual studies as input. - Results - In total, 17 studies with a cumulative total of 677 at-risk individuals and 805 healthy control subjects were included. Frequentist analyses did not reveal significant differences between at-risk individuals and healthy control subjects. Similar results were observed with Bayesian analyses, which provided strong evidence for the absence of meaningful brain activation differences across the entire brain. Region of interest analyses specifically focusing on the amygdala confirmed the lack of group differences in this region. - Conclusions - These results suggest that brain activation patterns in response to emotional stimuli are unlikely to constitute a reliable endophenotype of schizophrenia. We suggest that future studies instead focus on impaired functional connectivity as an alternative and promising endophenotype.
Online verfügbar 22. Juni 2022, Artikelversion 12. Dezember 2022
Gesehen am 07.06.2023